Consistent absence of BRAF mutations in salivary gland carcinomas - Nooshin Mohtasham; Hossein Ayatollahi; Narges Ghazi; Amirhossein Jafarian; Azam Roshanmir (Mashhad University of Medical Sciences, 2017)
Introduction: Malignant salivary gland tumors are rare entities. Despite advances in surgery, radiation therapy and chemotherapy, the rate of the mortality and five-year survival has not been improved markedly over the last few decades. The activation of EGFR- RAS-RAF signaling pathway contributes to the initiation and progression of many human cancers, promising a key pathway for therapeutic molecules. Thus, the objective of this study was to evaluate BRAF mutations in salivary gland carcinomas. Methods: We designed PCR- RFLP (Polymerase Chain Reaction -Restriction Fragment Length Polymorphism) and screened 50 salivary gland carcinomas (SGCs) including mucoepidermoid carcinoma (MEC), adenoid cystic carcinoma (AdCC) and polymorphous low grade adenocarcinoma (PLGA) for the BRAF V600E mutation. Results: PCR-RFLP analyses demonstrated no mutation in BRAF exon 15 for SGC samples at position V600, which is the most commonly mutated site for BRAF in human cancer. Conclusions: According to our results SGCs didn't acquire BRAF mutations that result in a constitutive activation of the signaling cascade downstream of EGFR, hence SGCs can be a good candidate for anti EGFR therapies.